Density Functional Study of Organocatalytic Cross-Aldol Reactions between Two Aliphatic Aldehydes: Insight into Their Functional Differentiation and Origins of Chemo- and Stereoselectivities - Fu, Aiping; Zhao, Chengyan; Li, Hongliang; Tian, Fenghui; Yuan, Shuping; Duan, Yunbo; Wang, Zonghua (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2013)
The chemo-, diastereo-, and enantioselectivities in proline and axially chiral amino sulfonamide-catalyzed direct aldol reactions between two enolizable aldehydes with different electronic nature have been studied with the aid of density functional theory (DFT) method. The potential energy profiles for the enamine formation between each aliphatic aldehyde and the catalyst confirm that two subject catalysts can successfully differentiate between 3-methylbutanal as an enamine component and α-chloroaldehydes as a carbonyl component. Transition states associated with the stereochemistry-determining C–C bond-forming step with the enamine intermediate addition to the aldehyde acceptor for proline and chiral amino sulfonamide-promoted aldol reactions are reported. DFT calculations not only provide a good explanation for the formation of the sole cross-aldol product between two aliphatic aldehydes both bearing α-methylene protons but also well reproduce the opposite syn vs anti diastereoselectivities in the chiral amino sulfonamide and proline-catalyzed aldol reactions.